Voluntary and controlled weight loss can reduce symptoms and proton pump inhibitor use and dosage in patients with gastroesophageal reflux disease: a comparative study. Issue 2 (17th December 2014) - de Bortoli, N.; Guidi, G.; Martinucci, I.; Savarino, E.; Imam, H.; Bertani, L.; Russo, S.; Franchi, R.; Macchia, L.; Furnari, M.; Ceccarelli, L.; Savarino, V.; et al.
Summary: A wide variety of pieces of evidence has suggested that obesity is associated with a significant increase in the risk for gastroesophageal reflux disease (GERD) symptoms and its complications. The aim of this study was to evaluate the effect of weight loss on reflux symptoms in overweight/obese patients with proven GERD. We enrolled overweight/obese patients with typical GERD symptoms and erosive esophagitis. At baseline, patients underwent detailed reflux symptoms evaluation and anthropometric assessment, and were divided into two treatment groups: group A received proton pump inhibitor (PPI) and a personalized hypocaloric diet and aerobic exercise; and group B received PPI and a 'standard of care diet'. The dietetic treatment was considered effective if at least 10% of weight loss was achieved within 6 months. All patients were evaluated in terms of anthropometric data, GERD symptoms, and PPI use. In group A, mean body mass index (BMI) decreased from 30.3 ± 4.1 to 25.7 ± 3.1 ( P < 0.05), and mean weight decreased from 82.1 ± 16.9 kg to 69.9 ± 14.4 kg ( P < 0.05). In group B, there was no change in BMI and weight. Symptom perception decreased ( P < 0.05) in both groups during PPI therapy, but a higher improvement was recorded in group A. In group A, PPI therapy was completely discontinued in 27/50 of the patients, and halved in 16/50. Only 7/50 continued the same PPI dosage. In group B, 22/51 halved the therapy and 29/51 maintained full dosage of therapy, but none was able to discontinue PPI due to a symptom recurrence. Overall, weight loss of at least 10% is recommended in all patients with GERD in order to boost the effect of PPI on reflux symptom relief and to reduce chronic medication use.